High mass photon pairs in ℓ+ℓ−γγ events at LEP - Dova, María Teresa (1992)
From the analysis of the reactions e + e- → ℓ+ℓ−(nγ) (ℓ = e,μ,τ) we observe four events, e+e−γγ and three μ+μ−γγ, with the invariant mass of the photon pairs close to 60 GeV. These events were selected from a data sample collected in the L3 detector corresponding to 950000 produced Z°'s. More data are necessary to ascertain the origin of these events.